Regulatory stress tests and bank responses: Heterogeneous treatment effect in dynamic settings - Karel Janda; Oleg Kravtsov (Charles University in Prague, Institute of Economic Studies (IES), 2019)
This paper investigates the impact of regulatory stress test framework in the European Union on the banks conduct and portfolio adjustments. Our findings suggest that the banks subject to regulatory stress testing tend to structure their portfolios with lower risk density. However this does not affect the dynamic of realized risk that is measured by the proportion of non-performing exposure in portfolios. We argue that the regulatory stress testing can incentivize banks to altering a mix of assets in their balance sheets towards less capital-intensive areas, and thus creating concerns on the systemic concentration of risks in certain type of assets. The evidence from our analysis indicate that the stress-tested banks do not engage in moral hazard behaviour i.e. increasing risk in portfolio or experiencing excessive loan growth. Therefore we show that this regulatory tool successfully fulfils its objective of promoting prudent risk management practices.
Keywords: G20; G21; G28; 330; Regulatory stress test; capital regulation; heterogeneous treatment effect; event study; instrumental variable